Mice harboring pathobiont-free microbiota do not develop intestinal inflammation that normally results from an innate immune deficiency - Chassaing, Benoit (PLoS One, 2018)
BACKGROUND: Inability to maintain a stable and beneficial microbiota is associated with chronic gut inflammation, which classically manifests as colitis but may more commonly exist as low-grade inflammation that promotes metabolic syndrome. Alterations in microbiota, and associated inflammation, can originate from dysfunction in host proteins that manage the microbiota, such as the flagellin receptor TLR5. That the complete absence of a microbiota (i.e. germfree conditions) eliminates all evidence of inflammation in TLR5-deficient mice demonstrates that this model of gut inflammation is microbiota-dependent. We hypothesize that such microbiota dependency reflects an inability to manage pathobionts, such as Adherent-Invasive E. coli (AIEC). Herein, we examined the extent to which microbiota mismanagement and associated inflammation in TLR5-deficient mice would manifest in a limited and pathobiont-free microbiota. For this purpose, WT and TLR5-deficient mice were generated and maintained with the 8-member consortium of bacteria referred to as “Altered Schaedler Flora” (ASF). Such ASF animals were subsequently inoculated with AIEC reference strain LF82. Feces were assayed for bacterial loads, fecal lipopolysaccharide and flagellin loads, fecal inflammatory marker lipocalin-2 and microbiota composition. RESULTS: Relative to similarly maintained WT mice, mice lacking TLR5 (T5KO) did not display low-grade intestinal inflammation nor metabolic syndrome under ASF conditions. Concomitantly, the ASF microbial community was similar between WT and T5KO mice, while inoculation with AIEC strain LF82 resulted in alteration of the ASF community in T5KO mice compared to WT control animals. AIEC LF82 inoculation in ASF T5KO mice resulted in microbiota components having elevated levels of bioactive lipopolysaccharide and flagellin, a modest level of low-grade inflammation and increased adiposity. CONCLUSIONS: In a limited-complexity pathobiont-free microbiota, loss of the flagellin receptor TLR5 does not impact microbiota composition nor its ability to promote inflammation. Addition of AIEC to this ecosystem perturbs microbiota composition, increases levels of lipopolysaccharide and flagellin, but only modestly promotes gut inflammation and adiposity, suggesting that the phenotypes previously associated with loss of this innate immune receptor require disruption of complex microbiota.